(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2012)
Book Review Poverty in Scotland 2011: Towards a more equal Scotland John H. McKendrick, Gerry Mooney, John Dickie and Peter Kelly (eds) 2011. Child Poverty Action Group ISBN 9781906076597. 240 pages